The Influence of Transformational Leadership on Organizational Performance (Case Study on the DIGNITY Student Association) - Abdillah, Sulthan Dzaki; A’la ‘Abid,; Desra Kusnandar,; Dzakwan Rafi Arrayan,; Fairuz Azka Azhari,; Alifsyah Alam, T.; Btari Mariska Purwaamijaya, (International Conference on Digital Business Innovation and Technology Management (ICONBIT), 2024)
This study examines the influence of transformational leadership by the Board of Commissioners on the organizational performance of the DIGNITY student association. The results show transformational leadership practices, including idealized influence, inspirational motivation, and individual consideration, have a significant positive impact on DIGNITY's performance. The Board's use of an AI chatbot to gather student feedback demonstrates adaptation to digital-era governance. The findings contribute to understanding transformational leadership in student organizations engaged in digital business. Statistical analysis confirmed the validity and reliability of the measurements used. Overall, the study validates that investing in transformational leadership within student organization governance can yield meaningful improvements in organizational outcomes.